TREND PENGGUNAAN NOSQL UNTUK BASIS DATA NON RELASIONAL - -, Mega Orina Fitri (Teknosains, 2013)
NoSQL is a non-SQL RDBMS which derived from RDB system, developed by Walter W. Hobbs at RAND Organisation. NoSQL uses UNIX as itâs operating system. A NoSQL database is exactly the type of database that can handle the sort of unstructured, messy and unpredictable data that our system of engagement requires. This database can be used as alternative rather than RDBMS and its SQL. This paper explained many things about NoSQL and how to modeling database with NoSQL. NoSQL itself has many advantages : elastic scaling, big data, eliminate DBA, economic, and flexible data model. However, it has challenges as well. The challenges are about the maturity. support, analytic and business intelligence, administration, and expertise.Key words : database, non-relational, nosql, rdbms